2016
DOI: 10.1021/acsphotonics.6b00201
|View full text |Cite
|
Sign up to set email alerts
|

Optical Chirality Flux as a Useful Far-Field Probe of Chiral Near Fields

Abstract: To optimize the interaction between chiral matter and highly twisted light, quantities that can help characterize chiral electromagnetic fields near nanostructures are needed. Here, by analogy with Poynting's theorem, we formulate the time-averaged conservation law of optical chirality in lossy dispersive media and identify the optical chirality flux as an ideal far-field observable for characterizing chiral optical near fields. Bounded by the conservation law, we show that it provides precise information, una… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(148 citation statements)
references
References 60 publications
2
134
0
Order By: Relevance
“…For absorption-less scattering objects consisting of isotropic materials, the conversion of helicity due to the scatterer vanishes when the integrated optical chirality flux into the structure is equal to the integrated outgoing flux. 35,36 We see in The symmetry of the disk upon reflection across any plane containing the optical axis ensures that the results for incident right circularly polarized light would be identical except for a sign change in the signed quantities. From these calculations it can be concluded that the cylinder meets the three requirements, and can act as an approximately helicity preserving source of chiral near-fields for enhanced CD measurements.…”
Section: Resultsmentioning
confidence: 99%
“…For absorption-less scattering objects consisting of isotropic materials, the conversion of helicity due to the scatterer vanishes when the integrated optical chirality flux into the structure is equal to the integrated outgoing flux. 35,36 We see in The symmetry of the disk upon reflection across any plane containing the optical axis ensures that the results for incident right circularly polarized light would be identical except for a sign change in the signed quantities. From these calculations it can be concluded that the cylinder meets the three requirements, and can act as an approximately helicity preserving source of chiral near-fields for enhanced CD measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, one can determine the electron velocity en v j ) [55,57,59,69]. It should be emphasized that K is the helicity density, but not the chirality density (Lipkin's zilch); these quantities are simply proportional to each other only in free space [57,77,[98][99][100][101][102]. Similarly to equation (2.17), for a plane wave in a homogeneous transparent medium, equation (5.1) yields:…”
Section: Magnetization Magnetization Current and Abraham Momentummentioning
confidence: 98%
“…The practical use of other less well known conservation laws is being investigated. For example, the helicity conservation law is being considered in the context of chiral light-matter interactions [1][2][3][4]. The effects of the conservation laws of the two transverse components of angular momentum are also under scrutiny [2,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%